Impacts of COVID-19 on households in CAREC countries - Dina Azhgaliyeva; Ranjeeta Mishra; Trinh Quang Long; Peter J. Morgan (Asian Development Bank Institute (ADBI), 2022)
The impacts of the COVID-19 outbreak have heavily affected CAREC member countries, which include Afghanistan, Azerbaijan, Georgia, Kazakhstan, the Kyrgyz Republic, Mongolia, Pakistan, the People's Republic of China (PRC), Tajikistan, Turkmenistan, and Uzbekistan. The COVID-19 crisis and the resulting falls in demand and supply due both to uncertainty and policy measures such as lockdowns, "social distancing," and travel restrictions are having a severe impact on CAREC member countries. In order to better understand these impacts, computer-assisted telephone (CATI) interviews of households were conducted in ten countries from the CAREC region (excluding the PRC). This paper estimates the impact of COVID-19 on income declines, expenditure changes, and financial difficulty in December 2020 compared with June 2020.
Keywords: D14; G51; H12; H84; I10; I24; J6; 330; COVID-19; CAREC; Central Asia; household survey; household income; employment